STRATEGI BRANDING FAKUTAS TEKNOLOGI INDUSTRI PERTANIAN MELALUI PEMASARAN DIGITAL MENGGUNAKAN METODE AIDA (ATTENTION, INTEREST, DESIRE, ACTION) - Reina Rafa Zakiyah Armasta; Roni Kastaman; Faisal Syahmurman (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The number of tertiary institutions in Indonesia is increasing which can make competition even tougher, so that higher education institutions are required to have clear appeal or value through digital media so that people trust and can easily assess the image of a brand or college. One of the faculties at Padjadjaran University that utilizes digital marketing media as a branding strategy is FTIP. Therefore, this study aims to determine the attractiveness of new students to FTIP's branding strategy through digital marketing using the AIDA method (Attention, Interest, Desire, Action). This research is included in the type of quantitative research through a descriptive approach and using purposive sampling as a sampling technique with a total of 176 students as respondents. Researchers used the analysis of normality test, t test, F test and multiple linear regression using SPSS 28.0 software. The results of the study stated that there was a correlation between digital marketing using the AIDA model and the attractiveness of new students of 53.8%. So to get interest from prospective new students, FTIP can upload interesting and informative information, so that it will increase the attractiveness of prospective new students through Instagram social media.